New turtles (Chelonia) from the late Eocene through late Miocene of the Panama Canal Basin (2012)
Four distinct fossil turtle assemblages (Chelonia) are recognized from the Panama Canal Basin. The oldest, from the late Eocene–early Oligocene Gatuncillo Formation, is dominated by podocnemidid pleurodires. The early Miocene Culebra Formation includes both podocnemidids and trionychids. The early to middle Miocene Cucaracha Formation includes taxa classified in Geoemydidae (including Rhinoclemmys panamaensis n. sp.), Kinosternidae (represented by Staurotypus moschus n. sp.), large testudinids, trionychids, and podocnemidids, and finally, the late Miocene Gatun Formation records cheloniid sea turtles. These fossils include the oldest known representatives of Rhinoclemmys, the oldest record of kinosternids in Central America with a more extensive southern paleodistribution for Staurotypus and staurotypines in general, early occurrences of giant tortoises in the Neotropics, the oldest occurrence of soft-shell turtles in the tropics, the oldest late Eocene–early Oligocene Neotropical occurrences of podocnemidids. The Panamanian fossil turtles represent clades that are primarily endemic to North America, showing their very early arrival into the Neotropics prior to the complete emergence of the Isthmus of Panama, as well as their first contact with Caribbean-South American pleurodires by the early Miocene.